The Importance of Worldview Paradigms in Formation of the Conceptual Foundation Social Forecast - R. V. Fedorov; L. A. Pafomova (Дискурс, 2021)
Introduction. Forecasting in social philosophy is aimed at anticipating and forming a conceptual image of the future society. The methodological basis for constructing a development scheme for achieving the desired state of the social system is ideological and cultural-historical paradigms. A philosophical analysis of the historical process, despite all its diversity, allows us to identify fundamental determinants that are used for geopolitical shifts in the world. The unification of the nature of the interaction algorithms does not mean the exclusion of national interests and the levelling of the civilizational characteristics of the actors. The main goal is formulated in the context of the need to reach a compromise acceptable to all parties in the face of competition in the geopolitical space. In a situation of confrontation, attitudes aimed at one-sided gain will inevitably adjust the parameters of social forecast on the part of the actors who are regarded as the object of such influence.Methodology and sources. As a methodological basis for work, the authors use the philosophical methodology of comparative analysis on the material of worldview and political narratives in geopolitical scenarios, which are basic for the conceptual substantiation of ways to achieve specific political goals. The article analyzes the paradigm of civilisational globalisation and expert-prognostic recommendations substantiating influence mechanisms for the implementation of tasks aimed at isolation of social systems whose values, from the point of view of the Western political elite, are incompatible with liberalism.Results and discussion. The article examines the features of social forecasting, which are determined by the availability of an objective resource base for the implementation of the intended goals and the mechanism for making political decisions. Due to the large number of variables in society that affect the dynamics of its development, the presence of a subjective factor makes it possible to realize the variability of its development. Competition of the geopolitical interests of the main actors in the historical process increases the range of uncertainty in the ways and mechanisms for achieving the set goals. The subjects of political control determine the specifics of the formation of an adequate response in response to the doctrine of unipolar strategic domination. The mobilization of economic and political resources allows maintaining civilizations identity in opposition to expansionary geopolitical strategies.Conclusion. In the real world, liberal values do not have the status of general universality. Theoretical and methodological principles in the formation of social prognosis become the most important link in modern conditions. In the sphere of geopolitics, Russia should position itself as a humanitarian-oriented political force, ensuring the preservation of traditions and the identity of all peoples. This would help to create a platform for uniting social movements advocating similar world view positions in the political struggle.